2018
DOI: 10.1016/j.tra.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Where is the happy transit rider? Evaluating satisfaction with regional rail service using a spatial segmentation approach

Abstract: Public transit agencies are delivering transport services in a rapidly changing and highly competitive transportation market. Ensuring rider's satisfaction in such an environment has led several public transit agencies to adopt different marketing strategies. For example, market segmentation analyses are commonly employed by transit agencies to identify groups of users, which are subsequently used as a base for developing policies and strategies aimed at improving customer satisfaction. However, previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…These differences in city and region size mean different realities in the public transport systems. For instance, crowding is a common issue around large cities (see [38,41]), while other types of comfort-related attributes are more important in less densely populated areas (see [20,40,42,43]). Geographic context is indicated in the review when relevant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in city and region size mean different realities in the public transport systems. For instance, crowding is a common issue around large cities (see [38,41]), while other types of comfort-related attributes are more important in less densely populated areas (see [20,40,42,43]). Geographic context is indicated in the review when relevant.…”
Section: Resultsmentioning
confidence: 99%
“…Also, evidence from the suburban railway network in Paris suggests that passengers travelling for other purposes than commuting value punctuality even more than commuters [69]. A related issue is communicating information about service disruptions, which is highly valued among all passengers [41,69]. Specifically, explicit information about the expected duration of delays is particularly appreciated [69].…”
Section: Time 441 Reliabilitymentioning
confidence: 99%
“…When trying to understand the various transit systems passengers' behaviour and preference, a number of researchers suggested to pay attention to the passengers' background (Chakrabarti, 2017;Satiennam et al, 2016;Shen et al, 2016;Van Lierop & El-Geneidy, 2016;Ramezani et al, 2017;Grise & El-Geneidy, 2018;Newbold & Scott, 2018). Within their researches, they found that passengers' behavior and preference vary through various backgrounds.…”
Section: Passengers' Backgroundmentioning
confidence: 99%
“…Passengers' behavior and preference are not homogenous, though the magnitude of the heterogeneity may vary as well. Some researchers went further by classifying transit passengers into some groups and analyzing the behavior and preference of each group's members (Van Lierop & El-Geneidy, 2016;Grise & El-Geneidy, 2018;Newbold & Scott, 2018).…”
Section: Passengers' Backgroundmentioning
confidence: 99%
“…There are no uniform criteria for grading of the crowding levels, while it was mainly referred to as the passenger standing density. In some countries [29][30][31][32], such as Australia, The Netherlands, Chile, USA, etc., the standards for the passenger standing density were divided into two categories: the comfortable criterion with a standing density of three passengers per square meter and the crowding criterion with a standing density of six passengers per square meter. For example, in the US, the Transit Capacity and Quality of Service Manual (TCQSM) [33] provides guidance and reference for measuring passenger crowding.…”
Section: Measures To Track Passenger Crowdingmentioning
confidence: 99%